(untitled) (Research, Society and Development, 2021)
Objective: to evaluate the microbiological conditions of the beds in a Surgical Center of a public teaching hospital in the city of Belém, Pará. Methods: Samples of the surgical beds were collected after being vacated, using a swab roll moistened in sterile saline solution, before and after bed disinfection. The samples were processed in the Bacteriology Sector of the Clinical Analysis Laboratory of CESUPA-LAC / CESUPA. The antimicrobial sensitivity test was performed using the disk diffusion method using the Kirb Bauer technique and the result was expressed as sensitive, moderately resistant (intermediate) and resistant. Results: In the samples collected from the surgical beds, different species of the Staphylococcus genus were isolated: S. aureus, S. epidermidis and S. saprophyticus, which showed more resistance to Penicillin, Azithromycin and Vancomycin, respectively. After disinfection, there was a reduction in the species S. aureus and S. epidermidis and an increase in S. saprophyticus. Regarding Gram negative, of all samples collected, only in two they were positive, both being in the collection before disinfecting the beds. In the collection after disinfection, Gram negative samples were negative. Disinfection was more effective for Gram negative than Gram positive bacteria. Conclusion: Therefore, the microbiological analysis performed on surgical beds, before and after disinfection, demonstrated that they had a high microbial load, thus constituting a possible source of environmental contamination capable of triggering an infectious process.